Genetic determinants of antipsychotic-induced weight gain - Reynolds, Gavin (Henry Stewart Talks, 2007)
Antipsychotic drugs: limitations and side effects, Drug-induced weight gain, Severity and consequences, Receptor mechanisms, Role of 5-HT2C receptor, Pharmacogenetics of antipsychotic weight gain: 5-HT2C promoter polymorphism, Functional mechanism of polymorphism, Role of leptin and leptin-promoter polymorphism, Role of genetic testing, Future directions
Archived at 2021/02/25